Real-world outcomes from use of CDK4/6 inhibitors in the management of advanced/metastatic breast cancer in Asia. (December 2022) - Low, Jia Li; Lim, Elaine; Bharwani, Lavina; Wong, Andrea; Wong, Karmen; Ow, Samuel; Lim, Siew Eng; Lee, Matilda; Choo, Joan; Lim, Joline; Chan, Gloria; Walsh, Robert John; et al.
Background: Oestrogen receptor positive, human epidermal growth factor receptor-2 (HER2) negative breast cancer (BC) is the most frequently diagnosed BC subtype. Combinations of cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) with anti-oestrogen therapy have led to improved survival compared with anti-oestrogen therapy alone for advanced/metastatic BC. The evaluation of CDK4/6i in the real-world facilitates treatment planning, insights into the incidence of drug toxicities, dose modifications including dose delays (DDs) and dose reductions (DRs) and improves prognostic accuracy in subgroups, for example geriatric patients, who are under-represented in clinical trials. Methods: This multi-centre study analysed retrospective and prospective data from 456 patients treated with CDK4/6i between January 2015 and December 2020. We examined patient characteristics, variation in prescribing practices, efficacy and toxicity outcomes. Results: In all, 456 patients were included in this study. The median age was 59 (range: 24–92). In total, 85 (19%) were ⩾70 years old. In all, 122 (27%) and 119 (26%) of patients were treated in the first-line and second-line settings, respectively. In total, 25 (5%), 31 (7%) and 145 (32%) of patients had brain, peritoneum and liver metastasis, respectively, at the time of CDK4/6i initiation. On univariate analysis, heavily pre-treated patients and those with distant metastases, involving the liver, brain or peritoneum, had significantly shorter progression-free survival (PFS) and 24-month overall survival (OS). Elderly patients (⩾70) had a shorter PFS; OS results were not mature. Majority of patients ( n  = 362, 80%) initiated treatment with the United States FDA-approved starting dose of CDK4/6i. In all, 330 (72%) had at least one DD and 217 (48%) patients required at least one DR, but these dose modifications were not associated with poorer survival outcomes. Patients age ⩾70 were more likely to require dose modifications leading to a lower treatment dose. The most common reason for DD/DR was neutropenia (60%) and the incidence of febrile neutropenia was only 2%. Conclusions: Our study indicates CDK4/6i is effective and safe. Age ⩾ 70, distant metastases to liver, peritoneal or brain were negative prognostic factors. Age ⩾ 70 was associated with significantly increased requirement for dose modification; however, this did not impact survival outcomes. These findings provide reassurance that survival outcomes are not adversely affected in elderly patients when DD/DR is indicated.